Pengaruh Kualitas Pelayanan dan Inovasi Layanan terhadap Kepuasan Pelanggan PT PLN - Feriansyah Manik; Enda Surbakti; Mardhiatul Husna; Indra Siregar; Jamardua Haro (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
Currently, competition is increasingly fierce, especially in service-oriented companies, which are becoming more competitive with numerous firms offering services to the public with varying characteristics. Companies that aim to survive and grow must provide the best quality of service to achieve customer satisfaction. This is in line with service quality theory, which states that a company deemed to be of high quality meets consumer expectations and even exceeds them.This study aims to analyze the influence of service quality and service innovation on customer satisfaction at PT. PLN (Persero) in Kabupaten Pakpak Bharat, specifically in the village of Penaggalen Binanga Boang. The research adopts a quantitative approach, utilizing a saturated sampling method with 98 respondents who are customers of PT PLN (Persero) in Kabupaten Pakpak Bharat, residing in the village of Penaggalen Binanga Boang. Data were collected through online questionnaires and analyzed using SPSS with multiple linear regression analysis.The results indicate that service quality partially and significantly influences customer satisfaction at PT PLN (Persero) in Kabupaten Pakpak Bharat (case study in the village of Penaggalen Binanga Boang). Similarly, service innovation also partially and significantly affects customer satisfaction at PT PLN (Persero) in Kabupaten Pakpak Bharat (case study in the village of Penaggalen Binanga Boang). Both service quality and service innovation together have a positive and significant influence on customer satisfaction, with an F-value of 35.261 exceeding the critical F-value of 3.092. The significance value of 0.000 is less than the significance level of 0.05 (0.000 < 0.05), leading to the rejection of the null hypothesis (H0) and acceptance of the alternative hypothesis (H1).